Magnetic compression anastomosis with atypical anastomosis for anastomotic stenosis of the sigmoid colon: a case report - Teppei Kamada; Hironori Ohdaira; Sojun Hoshimoto; Satoshi Narihiro; Norihiko Suzuki; Rui Marukuchi; Hideyuki Takeuchi; Masashi Yoshida; Eigoro Yamanouchi; Yutaka Suzuki (Surgical Case Reports)
Abstract Background Magnetic compression anastomosis (MCA) is mainly applied in the gastrointestinal and biliary tracts through a nonsurgical procedure that can create an anastomosis similar to that obtained through surgery. Magnets usually adsorb in the end-to-end direction (end-to-end anastomosis), exert a strong magnetic force and create an anastomosis according to the size of the magnets. Regular endoscopic dilation is required to prevent restenosis when the anastomotic size is small. We report a case in which MCA was successfully used to treat anastomotic stenosis of the sigmoid colon; the magnets adsorbed in the side-to-side direction rather than the end-to-end direction and generated a wide anastomosis in a short time that did not require endoscopic dilation. Case presentation An 81-year-old woman was admitted to our hospital to treat anastomotic stenosis of the sigmoid colon for closure of transverse colostomy. Two years prior, the Hartmann operation and drainage were performed at other hospitals due to perforated diverticulitis of the sigmoid colon. Obstruction of the sigmoid colostomy occurred, and a transverse colostomy was performed. One year after the first surgery, high anterior resection was performed, but anastomotic stenosis occurred, causing obstruction. MCA was planned because the patient had a history of multiple operations and was expected to have strong adhesions postoperatively. MCA was safely performed, but two magnets were accidently adsorbed in the side-to-side direction. The magnet position could not be changed. The two magnets were expected to move and adsorb in an end-to-end direction naturally due to bowel movements. The magnets that adsorbed in the side-to-side direction dropped from the anus 5 days after treatment, and the anastomosis was observed by colonoscopy. Three ileus tubes were placed from the transverse colostomy beyond the anastomosis to prevent restenosis. Colonoscopy showed that the anastomosis diameter was wider than expected at 14 days after treatment, and endoscopic dilation was not necessary. No complications were observed in this patient’s postoperative course. Finally, closure of the patient’s colostomy was successfully performed. Conclusions MCA with side-to-side anastomosis generated a wide anastomosis in a short time.